Analisa Ramalan Produksi Pot Bunga Pada KUPR Rorre-Waitatiri Maluku Tengah - Zisilya Kastanya; Stenly Titioka; Febiola Matuankotta (P3M Politeknik Negeri Ambon, 2024)
KUPR Rorre is a company engaged in the production, which produces furniture and home furnishings. The products produced by KUPR Rorre such as chairs, tables, curtains, partitions, shelves and parsets are in accordance with consumer demand, besides that there are also flower pot products whose production is carried out continuously, this results in the company always having excess production from year to year. The purpose of this study is to calculate and analyze the forecast of flower pot production in KUPR Rorre for the next 3 years from 2020-2022. The analysis used in this study is Linear Trend Analysis with the Least Squares Method using the equation formula Y = a + bx and to determine the accuracy of the forecast that has been known using the standard Error Of Estimate Analysis. From the results of the forecast analysis, it is hoped that KUPR Rorre can be used as an input in developing company activities, especially in knowing the number of products that must be produced. The results of the Linear Trend Analysis calculation can be seen that the forecast of flower pot production in KUPR Rorre is in 2020 as many as 786 units of flower pots, in 2021 as many as 798 units of flower pots, and in 2022 as many as 810 units of flower pots. The Standard Error of Estimate analysis calculation shows that the error level of the production browser calculation results is 36 units of flower pots. These figures can be a reference for KUPR Rorre to plan the number of products that must be produced to meet consumer needs. Keyword: Forcasting Production